Correlation between retinal nerve fiber layer thickness and anthropometric parameters in young adult Malay subjects - Mohd Hashim, Farhi; Ithnin, Mohd. Hafidz; Othman, Shah Farez; Jaafar, Nurul Hazirah; Tamchek, Nizam (Academic Strive, 2025)
Introduction: Retinal nerve fiber layer (RNFL) is one of the layers of the retina in our eye that are composed of axons of the retinal ganglion cells which are responsible to transmit our visual input to the brain. Furthermore, there was a study stated that RNFL abnormalities are also linked with obesity. An individual’s body composition and general physical attributes are typically evaluated using anthropometric parameters, such as height, weight, body mass index (BMI), waist circumference, and waist-to-hip ratio. Aim: The goal of the study is to establish a correlation between RNFL thickness and anthropometric measurements in young adult Malay subjects by determine the mean RNFL thickness and anthropometric measurements. Methodology: Thirty (30) Malay subjects aged 19 to 25 years old and free from any surgery or disease (ocular and systemic) were recruited. RNFL thicknesses were measured using the swept-source optical coherence tomography (SS-OCT), and anthropometric measurements, i.e., height, weight, waists were conducted. Results: No significance correlations were found between the RNFL thickness and anthropometric measurements (p>0.05). Conclusion: Our results suggest that there is no relationship between RNFL thickness and anthropometric parameters in Malay subjects.